ANALYSIS OF PRAGMATIC POLITENESS STRATEGIES IN FRANZ KAFKA’S NOVEL THE METAMORPHOSIS - Muhammad Saddam; Yasmin Elfa Mediena; Aidil Syah Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This study explores the pragmatic politeness strategies employed in Franz Kafka’s novel "The Metamorphosis." Utilizing Brown and Levinson's (1987) politeness theory, the research analyzes how the characters navigate social interactions and maintain relationships in the context of Gregor Samsa’s transformation. The analysis reveals a dynamic use of bald on-record, positive politeness, negative politeness, and off-record strategies throughout the novel. Initially, the family’s interactions with Gregor are characterized by positive politeness strategies aimed at preserving normalcy. However, as Gregor's condition deteriorates, negative politeness and off-record strategies become more prominent, reflecting growing emotional and psychological distance. The father's frequent use of bald on-record strategies underscores the collapse of familial bonds and the rise of authority and control. These findings align with existing theories on politeness and impoliteness, demonstrating their applicability to literary analysis. The study also highlights Kafka’s depiction of alienation and existential angst through the characters' evolving politeness strategies. By examining the shifts in these strategies, the research provides insights into the social dynamics and psychological states within the Samsa family. This analysis contributes to the broader discourse on the intersection of language, society, and literature. The study underscores the importance of context in understanding politeness and its role in shaping character interactions and narrative themes.